Students' Perception of Google Classroom for English as a Foreign Language Writing Courses - Andhi Dwi Nugroho; Titi Lestari (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2021)
The study aimed to expose the students’ perception of Google Classroom for EFL writing courses at high school levels. The study applied descriptive qualitative design applying phenomenology. The subjects in this study were 60 students of three vocational schools in Yogyakarta, Indonesia. The data were gained from two instruments, questionnaire and interview. The data were analyzed using thematic analysis. The analysis results showed the students perceptions how they viewed Google Classroom as learning management system used in the writing courses. In terms of students’ perception, the study concluded that the students reported some benefits and challenges regarding Google Classroom based on their experience.